Influência do laser de diodo na resistência de união à dentina e da superfície irradiada na evaporação do solvente de sistemas adesivos - Friedrich, Luciana Roggia (2017)
This study aimed to evaluate, in vitro, the bond strength to dentin and the influence of their radiated surface (glass and dentin) on the evaporation degree of solvent of adhesive systems by the use of high power diode laser. It was performed in two stages, which consisted in: a) evaluating the bond strength (μSBS) through the microshear test. For this, 48 healthy third molars were selected, which were sectioned longitudinally, obtaining dentin disks. The specimens were randomly divided into 8 groups (n = 6) as a function of the adhesive system (Adper Scotchbond Multi-Purpose, Adper Single Bond 2, Clearfill SE Bond, and Optibond All-in-one) and no irradiation or irradiation with high power diode laser (experimental technique x control technique). The diode laser was applied continuously, perpendicularly and at a distance of 1 cm from the irradiated surface, at a power of 3 W for a time of 25 seconds. In the course, a cylindrical matrix of starch adhered to dentin, composite resin restora were made, which were stored for 24 hours at 37°C, and then submitted to the microshear test in the universal testing machine, using 1.0 mm/min speed until failure occurs; b) to evaluate the influence of their radiation surface on the evaporation degree of solvent (ED) by the gravimetric method. The groups were distributed according to adhesive systems (Adper Single Bond 2 and Clearfil SE Bond) and their radiation surface (glass and dentin). For the dentin surface, 12 human third molars had class I cavities made. For both evaluated surfaces, 10μL of each of the tested products were dispensed and the weight loss was measured. For each material, six monitoring series (n = 6) were taken. The ED and μSBS data were submitted to variance analysis, t-student test and/or Tukey’s test ( = 5%). Based on the values obtained from μSBS , the laser promoted higher μSBS values for the conventional adhesives when compared to the self-etch agents, being superior to the control technique for Adper Single Bond 2. In relation to the ED, the diode laser at a power of 3 W from 15 s, caused greater evaporation of the solvents in the conventional adhesive system when compared to the self-etch. In relation to their radiation surface, in almost all the times used, the laser caused greater evaporation of the solvents when their radiated surface was the glass. In this way, the diode laser appears as a new method, being dependent on the characteristics inherent to each adhesive system and their radiated surface.